Faktor – Faktor Yang Mempengaruhi Kenaikan Jumlah Pembiayaan Pada BSI KCP Kampung Pajak - indah wahyuni; Muhammad Lathief Ilhamy (Jurnal Akuntansi Keuangan dan Bisnis, 2023)
This study analyzes what are the other factors that influence the amount of increase in financing at indonesian sharia banks, especially at the BSI KCP of the tax village. What are the external factors and internal factors and why can this happen. This study used a descriptive qualitative research approach in which the data was collected through interviews and observations, as well as uring primary and secondary data sources. The result of this study are the results showing that the factors that influence the increase in the amount of financing at the BSI KCP of the tax village are the level of profit sharing, third party funds, non perfoming financing (NPF), return on assets (ROA) and the ratio of operating costs and operating income (BOPO). ROA and BOPO, which illustrate the level of Bank profitability, do not have a significant effect because most of the funds channeled for financing come from third party funds (DPK) and do not come from profits earned by the Bank.